Cre Recombinase Strains Used for the Study of Adipose Tissues and Adipocyte Progenitors. Issue 10 (10th April 2017) - Liu, Jiaqi; Xu, Ziye; Wu, Weiche; Wang, Yizhen; Shan, Tizhong
Abstract : Adipose tissues play important roles in whole body energy homeostasis and lifer span. Understanding the mechanisms of controlling adipose tissues development is significant for providing useful information to treat the worldwide epidemic of obesity and its associated metabolic diseases. Several different Cre transgenes have been generated and used for determining the origin of adipose tissues and the function of individual gene in regulating adipose growth and development. Here, we mainly review and discuss the efficiency and specific of those Cre recombinase mouse strains used for the study of adipose tissues and adipocyte progenitors. J. Cell. Physiol. 232: 2698–2703, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We mainly review and discuss the efficiency and specific of those Cre recombinase mouse strains used for determining the origin of adipose tissues and the function of individual gene in regulating adipose growth and development.